2019
DOI: 10.1038/s41598-019-56888-9
|View full text |Cite|
|
Sign up to set email alerts
|

Adaptation of muscle activation after patellar loading demonstrates neural control of joint variables

Abstract: We evaluated whether the central nervous system (CNS) chooses muscle activations not only to achieve behavioral goals but also to minimize stresses and strains within joints. We analyzed the coordination between quadriceps muscles during locomotion in rats before and after imposing a lateral force on the patella. Vastus lateralis (VL) and vastus medialis (VM) in the rat produce identical knee torques but opposing mediolateral patellar forces. If the CNS regulates internal joint stresses, we predicted that afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…As described in ref. 28, we found that the ratio between VM and VL was altered systematically as the spring was attached and detached, consistent with regulation of the net mediolateral force on the patella (i.e., compensating for the lateral patellar load). Note that VI activity was not recorded in these animals.…”
Section: Methodssupporting
confidence: 74%
See 3 more Smart Citations
“…As described in ref. 28, we found that the ratio between VM and VL was altered systematically as the spring was attached and detached, consistent with regulation of the net mediolateral force on the patella (i.e., compensating for the lateral patellar load). Note that VI activity was not recorded in these animals.…”
Section: Methodssupporting
confidence: 74%
“…7B). Previous results from our laboratory demonstrated that the CNS adjusts the balance between VM and VL activity to compensate for this lateral patellar force (28). If the CNS regulates joint stresses and strains, the covariation between the activity of VL and VM should be unaffected by this change in balance so that the net mediolateral force on the patella remains consistently low.…”
Section: Correlation Between Vl and Vm Activation Intensities Across mentioning
confidence: 88%
See 2 more Smart Citations
“…Previous investigations using animal models presented evidence that the CNS uses muscle synergies (low dimensional modules) and combines them linearly to perform a motor task [1,2]. The central nervous system (CNS) chooses muscle activations to perform daily tasks and to prevent the stresses and strain that occur in the joints [3,4]. These muscle synergies encode information about muscle coactivation patterns within CNS for movement.…”
Section: Introductionmentioning
confidence: 99%